Вербалізація атрибута довгий в українській картині світу - Журавель, Мар’яна (Видавництво Львівської політехніки, 2017)
In this article verbalization of attribute 'long' based on the Ukrainian language phraseology material is explored and prototypical diatopical exposition available in Ukrainian linguistic image is analysed.
Keywords: фразеологія; прототип; атрибут; довгий; час; простір